P246 The in vitro effect of commonly used vasodilators on human pulmonary artery. (15th November 2016) - Hussain, A; Bennett, R; Kotidis, K; Chaudhry, M; Qadri, S; Cowen, M; Morice, A; Loubani, M
Abstract : Introduction: Acute pulmonary hypertension following cardiac surgery can have a significant effect on post-operative morbidity and mortality. The phosphodiesterase inhibitor sildenafil and the nitric oxide donor Sodium-Nitroprusside (SNP) are commonly used to treat pulmonary hypertension. The aim of this study was to characterise the pharmacological effects of clinically used vasodilators on the human pulmonary vasculature in comparison to the endogenous pulmonary vasodilators Atrial Natriuretic Peptide (ANP) and Brain Natriuretic Peptide (BNP). Methods: Research ethics committee approval was obtained for the use of human tissue for this study. Patients undergoing lung resection were consented for their resected lung tissue to be included in the study. Patients under the age of 18 and who cannot give informed consent were excluded from the study and twelve patients were enrolled in this study. Pulmonary arteries were dissected from disease free areas of lung resection and 35 PA rings of internal diameter 2–4 mm and 2 mm long were prepared. PA rings were mounted in a multiwire myograph system containing Krebs-Henseleit solution (aerated with 21% O2 : 5% CO2 at 37 o C) for measuring changes in isometric tension. A basal tension of 1.61 g was applied and the rings left to equilibrate for 60 min. After equilibration rings were pre-constricted to 11.21 µM PGF2α (EC80 ) then concentration response curves were constructed to Sildenafil, SNP, ANP and BNP by cumulative addition to the myograph chambers. The Integrity of the endothelium was confirmed with 1 μM Acetylcholine and smooth muscle viability was confirmed by exposure to potassium chloride. Results: ANP was the most potent and effective vasodilator whereas BNP had little effect. SNP was marginally less potent and effective than ANP and the maximum effect of sildenafil was about 50% that of ANP. The EC50 for ANP, BNP, Sildenafil and SNP were 1.105 nM, 28.78 nM, 1.06 uM and 22.6 nM respectively. Conclusion: This study demonstrated the differential effect of commonly used agonists on pulmonary vascular reactivity and this is the first comparison of these agents in human pulmonary arterial tissue. These effects may need to be considered in the clinical setting.